Case Report: Low-grade glioma with NF1 loss of function mimicking diffuse intrinsic pontine glioma - Bernstock, Joshua D.; Karandikar, Paramesh V.; Chen, Jason A.; Seidlitz, Jakob; Friedman, Gregory K.; Meredith, David M.; Liu, Kevin X.; Haas-Kogan, Daphne; Reardon, David A.; Peruzzi, Pier Paolo (Frontiers in Surgery, 2024)
Intrinsic, expansile pontine tumors typically occur in the pediatric population. These tumors characteristically present as diffuse intrinsic pontine glioma (DIPG), which is now considered as diffuse midline glioma (DMG), H3K27-mutated of the pons. DIPG has limited treatment options and a poor prognosis, and the value of tissue diagnosis from an invasive biopsy remains controversial. This study presents the case of a 19-year-old female with clinical and imaging hallmarks of DIPG, who underwent a biopsy of a tumor in the region of the right middle cerebellar peduncle. Her lesional cells were negative for H3K27M alterations and had low-grade histologic features. Next-generation sequencing revealed a frameshift mutation in the NF1 gene as the likely driver mutation. These features suggest a diagnosis of a low-grade glioma associated with NF1 loss of function, with far-reaching consequences regarding both treatment strategy and prognosis. This case provides support for the utility of diagnostic tissue biopsy in cases of suspected DIPG.